Improving Students’ English Pronunciation Ability Through Go Fish Game and Maze Game - Nurhayati, Dwi Astuti Wahyu (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
The problem highlighted in this research is the low pronunciation ability of Kindergarten students in Al-Irsyad Madiun that is caused by (1) the uninteresting activities in learning English; (2) the students' difficulties in pronunciating English words; (3) the students' low motivation in learning. The theoretical review includes the young learners characteristics, games in language, games for young learners. The procedure of the research consists of identifying the problem, planning the action, implementing the action, observing the action, and reflecting the result of the research. In this research, the researcher acts as the teacher who conducts the action research in the classroom and she is helped by the classsroom teacher. In collecting the data, the researcher uses observational technique supported with tests. In analyzing the data, the researcher uses the field notes, teacher's diaries, students ‘work supported with the cassette recording and photograph,then also compares the result of the students' pre-test and post-test to answer the research questions. There is significant improvement in the result of pre-test and post-test of cycle 1 and 2. In cycle 1, t0 (2.55734) is higher than tt (1.73) and in cycle 2, t0 (6.765738) is also higher than tt (1.73). From these two results, therefore, h0 is rejected and the alternative hypothesis (ha) is accepted. They practice their pronunciation through taking turn and asking each other for cards to match those they have in their hands, arranging a word and sticking on alphabet, pronunciating the word, giving the meaning, hen making a sentence such as Go Fish Game and Maze Game. By conducting these games, using interesting media, creating various interesting tasks and activities can increase the students' motivation in learning English and pronunciation ability.Keywords: Improving, pronunciation, ability, go fish and Maze games